Remedy Through Paradox? Constructions of Internal Legitimacy in a Publicly Discredited Organization. (November 2014) - Breit, Eric
This article examines how members of publicly discredited organizations discursively construct senses of internal legitimacy. Drawing on a case study of the Norwegian Labor and Welfare Administration—an organization that has been subject to lengthy and persistent public criticism—four paradoxical relations between discourses are identified and critically examined: acknowledgment/denial, voice/silence, unity/fragmentation, and image/substance. Based on the findings, three arguments are made: First, talk by members of discredited organizations about their organization, their organizational selves, and the criticism offers crucial resources for the construction of internal legitimacy. Second, constructions of internal legitimacy require members to relate to and navigate between paradoxes. Third, despite the complexity they impose, paradoxes provide members of discredited organizations with significant room for managing their internal legitimacy.